Electrolyte
By using pentaerythritol bicyclic sulfate and tris(trimethylsilyl)phosphite as additives in the electrolyte solution, the gas production and interface stability problems of high-nickel silicon-based lithium-ion secondary batteries at high temperatures are solved, and the battery's high storage stability and good electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411886389.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-01
AI Technical Summary
High-nickel silicon-based lithium-ion secondary batteries have gas production problems in high temperature environments. The SEI film has poor stability, low interface stability of the electrode sheet, and corrosive substances in traditional electrolytes accelerate the rupture of the SEI film, resulting in the inability to exert electrochemical performance.
Pentaerythritol bicyclic sulfate and tris(trimethylsilyl)phosphite were used as specific additives, and the proportion within a specific range was controlled to prepare an electrolyte with high storage stability, low SEI film impedance, good interface and thermal stability.
It significantly reduces the growth rate of DCR during the battery cycle, maintains low gas production at high temperatures, and ensures the cycling performance and long life of the battery.
Smart Images

Figure BDA0005199412030000131 
Figure BDA0005199412030000141 
Figure BDA0005199412030000151
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an electrolyte. Background Art
[0002] High-nickel silicon-based lithium-ion secondary batteries refer to a new type of secondary battery that uses high-nickel binary or ternary materials for the positive electrode and silicon-based materials for the negative electrode. This type of secondary battery has a high theoretical energy density, but in actual applications, especially in high temperature environments, due to the volume effect of silicon-based materials, the SEI film formed on the surface has poor stability and the interface stability of the pole piece is low, which leads to serious gas production problems in the battery and cannot achieve the expected electrochemical performance; at the same time, the corrosive substances such as hydrofluoric acid contained in the electrolyte of traditional silicon-based lithium-ion batteries will accelerate the rupture of the SEI film to a certain extent, further worsening the gas production of the battery.
[0003] In addition, due to the generally poor storage stability, some auxiliary ingredients with the function of inhibiting gas production in most electrolytes currently used in the preparation of high-nickel silicon-based lithium-ion secondary batteries have become ineffective or deteriorated, and normal effects cannot be achieved. Summary of the invention
[0004] The purpose of the present application is to overcome the shortcomings of the prior art and provide an electrolyte. The electrolyte described in the present application adopts pentaerythritol bicyclic sulfate and tris(trimethylsilyl)phosphite as specific additives, and controls both of them within a specific range. The electrolyte has high storage stability. When applied to high-nickel silicon-based lithium-ion secondary batteries, the SEI film formed on the surface of the negative electrode plate has a low impedance, good interface stability and thermal stability, which significantly reduces the DCR growth rate during the cycle process, and the gas production at high temperature can also be maintained at a low level.
[0005] To achieve the above-mentioned object, in a first aspect of the present application, the present application provides an electrolyte, comprising a first additive and a second additive;
[0006] The first additive and the second additive satisfy: a:b=(0.15-3):1, wherein a% is the mass percentage of the first additive in the electrolyte, and b% is the mass percentage of the first additive in the electrolyte;
[0007] The first additive is pentaerythritol bicyclic sulfate, and the second additive is tris(trimethylsilyl)phosphite.
[0008] In a second aspect of the present application, the present application further provides a secondary battery, comprising the electrolyte described in the present application.
[0009] The beneficial effects of this application are:
[0010] The present application provides an electrolyte. The electrolyte of the present application adopts pentaerythritol bicyclic sulfate and tris(trimethylsilyl)phosphite as specific additives, and controls both of them within a specific range. The electrolyte has high storage stability. When applied to a high-nickel silicon-based lithium-ion secondary battery, the SEI film formed on the surface of the negative electrode plate has low impedance, good interface stability and thermal stability, so that the DCR growth rate during the cycle process is significantly reduced, and the gas production at high temperature can also be maintained at a low level. DETAILED DESCRIPTION
[0011] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0012] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0013] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0014] The present application is further described below with specific embodiments:
[0015] An electrolyte comprising a first additive and a second additive;
[0016] The first additive and the second additive satisfy: a:b=(0.15-3):1, wherein a% is the mass percentage of the first additive in the electrolyte, and b% is the mass percentage of the first additive in the electrolyte;
[0017] The first additive is pentaerythritol bicyclic sulfate (TDT), and the second additive is tris(trimethylsilyl)phosphite (TMSPi).
[0018] In the electrolyte described in the present application, pentaerythritol bicyclic sulfate and tris(trimethylsilyl)phosphite are compounded together and can be reduced to generate different intermediate products when applied to secondary batteries. The SEI film formed by these two intermediates has excellent interface stability and thermal stability, and low impedance. Especially when used in high-nickel silicon-based lithium-ion secondary batteries, it can effectively protect the silicon-based negative electrode material in the negative electrode plate while ensuring the battery cycle performance, avoiding its exposure to the active interface, significantly reducing the gas production of the battery, and significantly reducing the DCR growth rate during the cycle process. If any one of them is replaced, or other matching additive systems are selected, the same effect cannot be achieved. At the same time, among the two specific additives, when pentaerythritol bicyclic sulfate is used as a film-forming additive, the impedance of the SEI film formed by the intermediate product is relatively low, and the introduction of tris(trimethylsilyl)phosphite can effectively make the formed SEI film passivate quickly on the surface of the negative electrode material, and improve the degree of protection of the SEI film to the negative electrode material. However, if the proportion of the two is not appropriate, the first additive and the second additive cannot be synergistically compounded, which may not only reduce the stability of the overall electrolyte, but also easily produce a large number of additional by-products due to the decomposition reaction of the second additive, reducing the overall stability of the electrolyte. At the same time, it is also impossible to take into account the rapid passivation of the SEI film and maintain the impedance of the formed SEI film in a small range, which ultimately weakens the cycle performance of the battery, and the DCR increases at a high rate. Therefore, the ratio of the two additives needs to be controlled within a specific range.
[0019] In some embodiments, a:b=0.15:1, 0.18:1, 0.2:1, 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1 or any two of the range values.
[0020] It should be noted that the mass percentage of the first additive and the second additive in the electrolyte of the present application is confirmed by GC-MS test, and the specific method is:
[0021] If the electrolyte of the test object is in the secondary battery, use the battery charging and discharging equipment to discharge the secondary battery to be tested. The discharge conditions are: current 0.3C, cut-off voltage 2.5V. After recording the battery number / barcode, disassemble the battery in the glove box (H2O≤0.1ppm, O2≤0.1ppm) to collect the electrolyte. There are three ways to collect the electrolyte: After removing the battery cover, ① If there is free electrolyte, use a pipette to collect the electrolyte into a 5mL sample tube and seal it with sealing glue to prevent electrolyte leakage. ② If there is no free electrolyte, use a hydraulic press (Beijing Hengaode Technology Co., Ltd. FY-30 hydraulic press) to continuously pressurize until free electrolyte appears, collect the electrolyte into the sample tube and seal it. ③ Add an appropriate amount of dichloromethane extractant to the battery and record the dichloromethane content. After adding dichloromethane, put the battery into an aluminum-plastic bag and seal it with a heat sealer. Transfer it to an ultrasonic oscillator and oscillate it for 12 hours to allow the electrolyte in the electrode to be fully mixed with dichloromethane. Then use a pipette to draw the mixture of dichloromethane and electrolyte into a 5mL sample tube, and seal the sample tube with sealing glue; inject the collected electrolyte sample into the Agilent Intuvo 9000 gas chromatograph-mass spectrometer for testing with a microinjector to obtain a GC-MS spectrum; dissolve the first additive and the second additive in the EMC solvent to prepare solutions of different concentrations, and inject them into the Agilent Intuvo 9000 gas chromatograph-mass spectrometer to obtain a standard GC-MS spectrum. Compare the GC-MS spectrum of the electrolyte to be tested with the standard GC-MS spectrum, and then determine the content of each component based on the peak area of each component in the electrolyte to be tested;
[0022] If the electrolyte to be tested is a finished product, a standard GC-MS spectrum comparison is directly performed to determine the component content without the need to collect the electrolyte.
[0023] In some embodiments, a:b=(0.2-2):1.
[0024] As mentioned above, the mass ratio of the first additive and the second additive affects the stability of the electrolyte and the formation and properties of the SEI film in the battery. When the mass ratio of the two is preferably within the above range, the stability of the electrolyte is higher, the film-forming speed of the two is faster, the passivation effect at the interface of the negative electrode plate is better, the protection strength of the negative electrode plate is higher, and the impedance of the formed SEI film is better.
[0025] In some embodiments, a+b=0.15-2.8%.
[0026] More preferably, a+b=0.18-2.5%.
[0027] The two additives in the electrolyte are introduced in the ratio described above to achieve good synergistic effect, and those skilled in the art can adjust the total amount of the two additives added according to actual needs. When the addition amount is preferably within the above range, the electrolyte can not only achieve lower SEI film layer impedance and better interface stability when used in the battery, but also the thermal stability of the electrolyte itself is higher, and the battery can achieve a longer cycle life and a smaller DCR growth level.
[0028] In some embodiments, the mass percentage of the first additive in the electrolyte is 0.05-1.5%.
[0029] Further preferably, the mass percentage of the first additive in the electrolyte is in the range of one or any two of 0.05%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%.
[0030] In some embodiments, the mass percentage of the first additive in the electrolyte is 0.1-1.5%.
[0031] Further preferably, the mass percentage of the first additive in the electrolyte is 0.1-1%.
[0032] When the mass ratio of the two additives is within the specified range of this application, the addition amount of the first additive and the second additive can be adjusted according to the actual battery requirements for SEI film formation rate and film formation effect and overall conductivity: the content of the first additive affects the initial impedance and interface stability of the interface film layer formed by the negative electrode plate. When it is preferably within the above range, the secondary battery prepared by the electrolyte can achieve better impedance of the electrode plate interface film layer.
[0033] In some embodiments, the mass percentage of the second additive in the electrolyte is 0.1-1.3%.
[0034] Further preferably, the mass percentage of the second additive in the electrolyte is within the range of one or any two of 0.1%, 0.2%, 0.3%, 0.5%, 0.75%, 0.8%, 1%, 1.2%, 1.3%.
[0035] In some embodiments, the mass percentage of the second additive in the electrolyte is 0.1-1%.
[0036] In some embodiments, the mass percentage of the second additive in the electrolyte is 0.1-0.6%.
[0037] The high film-forming efficiency and film stability of the second additive after film formation can, when used in combination with the first additive, enable the battery to simultaneously achieve lower gas production and higher cycle performance through a synergistic effect, especially in a high-temperature environment. When the second additive is preferably within the above range, the resulting electrolyte can achieve better negative electrode plate protection, and the degree of side reactions between the electrolyte and the electrode is lower.
[0038] In some embodiments, the electrolyte further includes a third additive, and the third additive includes at least one of 1,3-propane sultone (PS) and lithium difluorophosphate (LiPO2F2).
[0039] In some embodiments, the electrolyte further includes a solvent and a lithium salt.
[0040] In some embodiments, the solvent includes at least one of a carbonate solvent, a carboxylate solvent, an ether solvent, a sulfone solvent, a nitrile solvent, and a phosphate solvent.
[0041] Exemplarily, the carbonate solvent includes but is not limited to at least one of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC); the carboxylate solvent includes but is not limited to at least one of ethyl acetate, methyl formate, and 1,4-butyrolactone; the ether solvent includes at least one of dimethyltetrahydrofuran, tetrahydrofuran, and 1,2-dimethoxyethane; the sulfone solvent includes at least one of methyl sulfone and dimethyl sulfoxide; the nitrile solvent includes at least one of propionitrile, butyronitrile, 1-(2-cyanoethyl)pyrrole, and 1,3,6-hexanetrinitrile; the phosphate solvent includes at least one of trimethyl triphosphate and triethyl phosphate.
[0042] Further preferably, the solvent may also include but is not limited to at least one of fluorinated derivatives of carbonate solvents, fluorinated derivatives of carboxylate solvents, fluorinated derivatives of ether solvents, fluorinated derivatives of sulfone solvents, fluorinated derivatives of nitrile solvents, and fluorinated derivatives of phosphate solvents.
[0043] Illustratively, the fluorinated derivative of carbonate solvent includes, but is not limited to, fluoroethylene carbonate (FEC).
[0044] More preferably, the mass percentage of the carbonate solvent in the solvent is 10-80%.
[0045] Further preferably, the mass percentage of the carbonate solvent in the solvent is within the range of one or any two of 10%, 15%, 20%, 25%, 30%, 40%, 50%, 60%, 70%, 80%.
[0046] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium difluorobis(oxalatophosphate), lithium tetrafluorooxalatophosphate, and the like.
[0047] Further preferably, the concentration of the lithium salt in the electrolyte is 0.8 to 2.5 mol / L.
[0048] Further preferably, the concentration of the lithium salt in the electrolyte is in the range of one or any two of 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, 2.2 mol / L, and 2.5 mol / L.
[0049] The electrolyte described in the present application can be combined with suitable solvents, lithium salts and other additives according to actual needs after selecting the first additive and the second additive and controlling the mass ratio between the two. The solvent and lithium salt added in amounts within the above-mentioned preferred range can be compounded to effectively ensure that the stability of the electrolyte is at a higher level and the SEI film formed in the battery is more stable.
[0050] The embodiment described in the present application also provides a secondary battery, comprising the electrolyte described in the present application.
[0051] In some embodiments, the secondary battery further includes a positive electrode sheet and a negative electrode sheet; the positive electrode sheet includes a positive electrode material, and the negative electrode sheet includes a negative electrode material.
[0052] In some embodiments, the positive electrode sheet includes a current collector and a positive electrode material layer;
[0053] Further preferably, the positive electrode material layer comprises a positive electrode material, a binder and a conductive agent.
[0054] In some embodiments, the negative electrode sheet includes a current collector and a negative electrode material layer;
[0055] Further preferably, the negative electrode material layer comprises a negative electrode material, a binder, a thickener and a conductive agent.
[0056] In some embodiments, the positive electrode material comprises at least one of lithium nickel cobalt manganese oxide and doped lithium nickel cobalt manganese oxide; and the negative electrode material comprises a silicon-based material.
[0057] Further preferably, the positive electrode material comprises LiNi a Mn b Co c N dO2, wherein 0.9≤a≤0.95, 0.025≤b≤0.05, 0.025≤c≤0.05, 0≤d<0.1, a+b+c+d=1 and N is at least one of Al, Na, Ti, Nb, Zr, W, Fe, Cr.
[0058] Further preferably, the molar percentage of nickel element in the positive electrode material to the transition metal elements is ≥ 90%.
[0059] Further preferably, the molar percentage of nickel element in the positive electrode material to the transition metal element is 90-95%.
[0060] It should be noted that the test method for the molar percentage of nickel element in the positive electrode material of the secondary battery described in the present application to the transition metal element is as follows: disassemble the secondary battery in an empty state to obtain a positive electrode sheet, dry the positive electrode sheet at 80°C for 4 hours, place it in a sintering furnace at 400°C for 4 hours, and use a ceramic knife to scrape off the positive electrode active material powder;
[0061] Accurately weigh 0.5g of positive electrode active material powder, disperse it in 20ml of water, add 10ml of nitric acid, mix well and heat it. After the positive electrode active material powder is dissolved, dilute the material to 100ml with water to obtain a solution to be tested;
[0062] The solution to be tested was subjected to ICP test. The ICP test conditions were as follows: the transition metal element detection spectral wavelength was selected. According to the characteristics of the sample and the elements to be detected, appropriate ICP instrument working conditions were set, including a gas flow rate of 0.5 L / min and a power of 1150 W. The molar content of Ni in the element was tested by ICP to obtain the molar percentage of nickel in the positive electrode material to the transition metal element.
[0063] Further preferably, the positive electrode material comprises LiNi 0.9 Mn 0.05 Co 0.05 O2、LiNi 0.8 Mn 0.1 Co 0.1 O2、LiNi 0.7 Mn 0.1 Co 0.2 O2、LiNi 0.7 Mn 0.2 Co 0.1 At least one of O2.
[0064] In some embodiments, the silicon-based material includes a silicon-carbon composite material.
[0065] Exemplarily, the silicon-based material is a silicon-carbon composite material, and the silicon-carbon composite material can be prepared by a CVD (chemical vapor deposition) method, specifically, by infiltrating silane into a carbon material by a CVD method, and then heating and sintering to obtain the silicon-carbon composite material.
[0066] Those skilled in the art may also adopt other methods to prepare silicon-based materials according to actual conditions, or directly purchase commercial products, and are not limited to the above-mentioned silicon-carbon composite materials and their preparation methods.
[0067] Specifically, the silicon-carbon composite material includes silicon-containing oxide.
[0068] Further preferably, the negative electrode material also includes a carbon-based material.
[0069] When silicon-based materials are used as negative electrode active materials, their conductivity is low. In order to improve the conductivity of the overall secondary battery, those skilled in the art may add carbon-based materials with better conductivity, such as graphite materials, for compounding according to actual conditions.
[0070] Further preferably, the mass percentage of silicon element in the negative electrode material layer is 0.5-12.5%.
[0071] Further preferably, the mass percentage of silicon element in the negative electrode material layer is in the range of one or any two of 0.5%, 0.6%, 0.8%, 1%, 1.5%, 2%, 3%, 4%, 5%, 8%, 10%, 12%, 12.5%.
[0072] It should be noted that the mass percentage of silicon element in the negative electrode material layer of the secondary battery described in this application is tested by alkali dissolution-ICP method. Specifically, the negative electrode plate of the secondary battery is disassembled and cleaned with solvent DMC (dimethyl carbonate), soaked for 48 hours, and dried at 60°C to scrape the powder of the negative electrode active material layer; weigh the powder sample, place it in a nickel crucible pre-filled with potassium hydroxide, add a little potassium hydroxide to cover the surface of the sample, drip two drops of ethanol, place it on an electric furnace and heat it until the potassium hydroxide melts and dehydrates, then move it to a muffle furnace at 1100°C, keep it molten and keep it warm for 8 hours, take out the nickel crucible, and cool it slightly. Put it in a 300mL plastic beaker, add hot water for extraction, and wash out the crucible after the reaction. Add HCl to the extract for acidification and hydrogen peroxide for oxidation. After cooling, wash it out with water, transfer it to a 100mL volumetric flask, adjust the volume, and shake it well. After standing, take the solution into another 100mL volumetric flask, adjust the volume, shake it well, stand and clarify, and obtain the solution to be tested. At the same time, a blank solution was prepared as a control, that is, a solution sample was prepared without adding the test sample but was prepared according to the above steps.
[0073] ICP test was performed on the solution to be tested, the wavelength of the element detection spectrum was selected, and the experimental conditions were set: according to the characteristics of the sample and the solution to be tested, the wavelength of the element detection spectrum was selected, and the experimental conditions were set: gas flow rate 0.5L / min, power 1150W; Si element determination wavelength 288.158nm; ICP test of the Si content of the element
[0074] Further preferably, the mass percentage of silicon element in the negative electrode material layer is ≥10%, and the mass percentage of the second additive in the electrolyte is 0.3-0.5%.
[0075] When the positive electrode material and the negative electrode material in the secondary battery are respectively selected as high-nickel material and high-silicon material, the stability of the negative electrode material is low, which is easy to cause gas production problems, and the ion transmission efficiency cannot be guaranteed. When an electrolyte containing the first additive and the second additive of the present application is selected, and the ratio of the second additive is preferably within the above range, the battery can more preferably maintain the stability of the electrode material, lower gas production, higher ion transmission efficiency, and better electrochemical performance.
[0076] In some embodiments, the battery satisfies: T*b=14-250, wherein T°C is the temperature corresponding to the first exothermic peak when the negative electrode plate is subjected to differential scanning calorimetry at 0-400°C.
[0077] In some embodiments, the battery satisfies: T*b=14.5-195;
[0078] Further preferably, the battery satisfies: T*b=25-95;
[0079] The DSC temperature of the battery is related to the heat generation rate and heat generation inside the battery. If the DSC decomposition temperature is too low, the heat generation inside the secondary battery will be large, which will in turn cause increased gas production. When the amount of the second additive added is correlated with the DSC decomposition temperature of the battery itself during the preparation of the electrolyte, and is selected within the above-mentioned relationship range, the internal heat of the battery can be preferentially controlled to reduce the probability of gas production. At the same time, the influence of the decomposition products formed by the second additive in the electrolyte during the film formation process on the battery impedance can also be reduced, and the formed SEI film has higher stability, further optimizing the electrochemical performance of the battery.
[0080] It should be noted that the specific test method for T℃ described in this application is:
[0081] (1) The secondary battery is fully charged: discharged at 0.33C to 0% SOC; charged at 0.33C to 4.25V, with a cut-off current of less than 0.05C;
[0082] (2) The fully charged secondary battery was disassembled in a glove box, and the negative electrode was washed with DMC (dimethyl carbonate). After soaking for 2 hours and drying, a 4 mm diameter negative electrode was cut using a cutting machine and placed together with 20 μL of electrolyte in a platinum crucible. The crucible was then placed in a differential scanning calorimeter (DSC214) test chamber for testing. The heating rate was 5 K / min, the temperature range was 25°C to 400°C, and the protective atmosphere was nitrogen. The temperature corresponding to the first exothermic peak of the negative electrode was confirmed based on the test results. The preparation method of the electrolyte is as follows: EC, EMC, and DEC are mixed in a mass ratio of 1:1:1 to obtain a mixed organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the above-mentioned mixed organic solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0083] The present invention is further described below with specific examples, which are not to be construed as limiting the scope of the present invention:
[0084] Example 1
[0085] A secondary battery, the preparation method comprising the following steps:
[0086] (1) Preparation of positive electrode sheet: The positive electrode material, the conductive agent acetylene black and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 92:4:4, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector aluminum foil, and then dried, cold pressed and cut to obtain the positive electrode sheet; the positive electrode material is LiNi 0.9 Mn 0.05 Co 0.05 O2.
[0087] (2) Preparation of negative electrode sheet: The negative electrode material, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose, and the binder styrene butadiene rubber are dispersed in water at a mass ratio of 96.4:1:1.2:1.4, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector copper foil, and then dried, cold pressed, and cut to obtain the negative electrode sheet. The negative electrode material includes graphite and silicon-carbon composite material, and the mass ratio of the two is 9:1. The mass percentage of silicon element in the negative electrode material layer is 5%;
[0088] The silicon-carbon composite material is a commercially available silicon-carbon material.
[0089] (3) Preparation of the diaphragm: A PP diaphragm with an average pore size of 2 μm and an air permeability of 300 s / 100 mL was used as a substrate, and then an alumina ceramic coating was coated and dried to obtain a diaphragm containing a coating;
[0090] (4) The positive electrode sheet, the separator (coated with a 2 μm thick coating with the coating facing the positive electrode sheet), and the negative electrode sheet are stacked and wound in sequence to form a battery cell, and the battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected. After vacuum packaging, standing, forming, and constant capacity, the secondary battery is obtained.
[0091] The parameters of each electrolyte are shown in Tables 1 and 2.
[0092] Embodiments 2 to 29
[0093] A secondary battery, which is different from Example 1 only in that the components of the electrolyte are different. The results are shown in Tables 1 and 2.
[0094] Each electrolyte includes a first additive, a second additive, a third additive, a fourth additive, a lithium salt, and a solvent, wherein TDT (wt%) and TMSPi (wt%) represent the mass percentage of the first additive TDT and the second additive TMSPi in the electrolyte, respectively. The lithium salt is lithium hexafluorophosphate, M 锂 (mol / L) represents the concentration of lithium salt in the electrolyte, the third additive is PS, the fourth additive is LiPO2F2, PS (wt%), LiPO2F2 (wt%) represent the mass percentage of the third additive PS and the fourth additive LiPO2F2 in the electrolyte respectively.
[0095] Table 1
[0096] parameter TDT (wt%) TMSPi (wt%) a:b T℃ T*b Example 1 0.3 0.2 1.5:1 176 35.2 Example 2 1 0.5 2:1 188 94 Example 3 0.5 0.5 1:1 179 89.5 Example 4 1.5 0.5 3:1 195 97.5 Example 5 0.1 0.6 0.17:1 179 107.4 Example 6 0.2 0.4 0.5:1 185 74 Example 7 0.4 0.4 1:1 178 71.2 Example 8 0.3 0.2 1.5:1 180 36 Example 9 0.27 0.1 2.7:1 175 17.5 Example 10 0.1 0.5 0.2:1 152 76 Embodiment 11 1 1 1:1 150 150 Example 12 1.2 0.8 1.5:1 152 121.6 Example 13 0.4 0.4 1:1 179 71.6 Embodiment 14 0.7 0.5 1.4:1 190 95 Embodiment 15 0.5 1 0.5:1 149 149 Example 16 0.8 1.2 0.67:1 145 174 Embodiment 17 1.1 0.6 1.83:1 162 97.2 Embodiment 18 0.195 1.3 0.15:1 140 182 Embodiment 19 1.3 0.45 2.89:1 178 80.1 Embodiment 20 1.4 0.6 2.33:1 183 109.8 Embodiment 21 0.68 0.4 1.7:1 189 75.6 Embodiment 22 0.6 1 0.6:1 148 148 Embodiment 23 0.2 0.1 2:1 190 19 Embodiment 24 0.3 0.15 2:1 150 22.5 Embodiment 25 0.2 0.9 0.22:1 190 171 Embodiment 26 0.3 0.5 0.6:1 198 39.6 Embodiment 27 0.3 1 0.3:1 140 140 Embodiment 28 0.075 0.1 0.75:1 140 14 Embodiment 29 1.3 1.2 1.08:1 205 246 Comparative Example 1 1.5 0.25 6:1 165 41.25 Comparative Example 2 0.1 1 0.1:1 189 189
[0097] Table 2
[0098]
[0099]
[0100] Effect example
[0101] The lithium ion secondary batteries obtained in each embodiment and comparative example were tested as follows:
[0102] (1) Gas production test: Use battery charging and discharging equipment to discharge the secondary battery. The discharge conditions are: current 0.33C, cut-off voltage 2.5V, and then fully charge the battery at a constant capacity according to the following conditions;
[0103] Constant capacity - charge at a constant current of 0.33C to an upper voltage limit of 4.25V, charge at a constant voltage until the current is less than or equal to 0.05C, and then discharge at 0.33C to a lower voltage limit of 2.75V; this is a cycle, charge and discharge 3 times, and take the discharge capacity of the third cycle as the battery capacity;
[0104] Full charge: charge at 0.33C constant current to the upper limit voltage of 4.25V, and charge at constant voltage until the current is less than or equal to 0.05C;
[0105] After full charge, the secondary battery is tested for volume using the water displacement method, which is recorded as V0. The battery is placed in a 60°C oven for 60 minutes and then taken out. After the battery temperature drops to room temperature, the battery volume is tested again using the water displacement method and recorded as V1. The gas production of the battery during this storage period is the difference between V1 and V0. This value divided by the battery's fixed capacity is the gas production per ampere-hour of the secondary battery.
[0106] The specific steps of the above-mentioned drainage method for testing the volume of a secondary battery are as follows:
[0107] (i) Add an appropriate amount of pure water into the container and measure its density using a densitometer and record it;
[0108] (ii) Adjust the balance to a horizontal level and tared (tared before each secondary battery test);
[0109] (iii) immerse the secondary battery body and the tabs together in the solution, ensuring that the secondary battery does not contact the container wall, read the value after stabilization and record the value as T;
[0110] (iv) Turn off the balance and seal the container tightly to prevent evaporation of the reagent.
[0111] The volume calculation formula of secondary batteries is T / ρ liquid;
[0112] Among them, before storage and after storage, tests are performed respectively to obtain T0 and T1;
[0113] Then the difference between V1 and V0 is: V1-V0=T1 / ρliquid-T0 / ρliquid
[0114] Gas production at 60°C storage = (V1-V0) / secondary battery capacity;
[0115] (2) DCR test: The secondary battery is fixed in capacity, fully charged to 4.25V at 0.33C, constant voltage cut-off current is 0.05C, 0.33C discharge is adjusted to 50% SOC, left to stand for 2h, and discharged at 1C for 18s. The starting discharge voltage is recorded as V1, the voltage after 18s discharge is recorded as V2, and the 18s discharge current is recorded as I1. The internal resistance of the secondary battery DCR1 = |V1-V2| / I1.
[0116] Place the secondary battery in a 55°C constant temperature box, discharge it at a constant current of 0.33C, and then cycle it in the constant temperature box at a charge and discharge test rate of 1C / 1C for 300 cycles, with a cycle voltage of 2.5 to 4.25V;
[0117] After 300 cycles, the secondary battery was discharged at 0.33C to 50% SOC, left to stand for 2 hours, and then discharged at 1C for 18 seconds at 50% SOC. The internal resistance of the secondary battery after the cycle was tested to obtain DCR2.
[0118] Then the DCR growth rate of the secondary battery = (DCR2-DCR1) / DCR1×100%. The test results are shown in Table 3.
[0119] Table 3
[0120]
[0121]
[0122] From Table 3 we can see that:
[0123] (1) The electrolyte described in the present application is based on pentaerythritol bicyclic sulfate and tris(trimethylsilyl)phosphite as specific additives in a specific ratio. It not only has high thermal stability and is not easily decomposed due to high temperature, but also helps to form a SEI film layer on the negative electrode sheet when applied to lithium-ion secondary batteries. The film has low impedance and has interface stability and thermal stability. Therefore, the DCR growth rate of the secondary battery is low and can be maintained within 4%. At the same time, the gas production performance can also be maintained at a low level. The gas production after cycling can be maintained within 4mL / Ah. In contrast, if the matching ratio is inappropriate, as shown in the products of Comparative Examples 1 and 2, the product cannot take into account both the performance of gas production and DCR growth rate.
[0124] (2) From the performance comparison of the products of Examples 1 to 27, it can be seen that the content ratio of the first additive and the second additive in the electrolyte has a great influence on the performance of the product, especially when the mass percentage ratio of the two is preferably in the range of (0.2 to 2): 1, the synergistic effect of the two additives is stronger; on the other hand, the mass percentage of the first additive and the second additive in the electrolyte will also affect their effectiveness. The amount of the first additive added will affect the impedance of the SEI film layer on the surface of the negative electrode plate, while the amount of the second additive added will affect the film formation efficiency of the SEI film, the stability of the film layer and the stability of the electrolyte itself. Therefore, when the ratio of the two is preferably within the above range, if the content of the first additive is further controlled within the range of 0.1 to 1%, and the content of the second additive is further controlled within the range of 0.1 to 0.6%, the DCR growth rate of the secondary battery is further controlled within 2.5%, and the gas production can be maintained within 2.7 mL / Ah.
[0125] (3) In addition, by regulating the amount of the second additive added and the selection of other components of the electrolyte, the exothermic temperature range of the negative electrode plate in the secondary battery, that is, the thermal range of the side reaction between the negative electrode plate and the electrolyte, can be regulated. According to Examples 1 to 29, especially Examples 21 to 29, it can be seen that when the compounding ratio of the two additives is within the preferred range, T*b is preferably in the range of 14.5 to 195, which can make the internal thermal stability of the secondary battery better and the heat generation efficiency lower, thereby reducing the gas production efficiency of the secondary battery. The DCR growth rate of the secondary battery can be maintained above 3.5%, and the gas production can be maintained within 3 mL / Ah. When T*b is preferably in the range of 25 to 95, the comprehensive performance of the product is better.
Claims
1. An electrolyte, characterized in that: including a first additive and a second additive; The first additive and the second additive satisfy: a:b=(0.15-3):1, wherein a% is the mass percentage of the first additive in the electrolyte, and b% is the mass percentage of the first additive in the electrolyte; The first additive is pentaerythritol bicyclic sulfate, and the second additive is tris(trimethylsilyl)phosphite.
2. The electrolyte according to claim 1, characterized in that The a:b=(0.2~2):
1.
3. The electrolyte according to claim 1, characterized in that The mass percentage of the first additive in the electrolyte is 0.05-1.5%, and / or the mass percentage of the second additive in the electrolyte is 0.1-1.3%.
4. The electrolyte according to claim 3, characterized in that The mass percentage of the first additive in the electrolyte is 0.1-1%, and / or the mass percentage of the second additive in the electrolyte is 0.1-0.5%.
5. The electrolyte according to claim 1, characterized in that The electrolyte also includes a solvent and a lithium salt; The solvent includes at least one of a carbonate solvent, a carboxylate solvent, an ether solvent, a sulfone solvent, a nitrile solvent, and a phosphate solvent; the lithium salt includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium difluorobis(oxalatophosphate), lithium tetrafluorooxalatophosphate, and the like.
6. A secondary battery, characterized in that: The electrolyte comprises the electrolyte according to any one of claims 1 to 5.
7. The secondary battery according to claim 6, characterized in that: The secondary battery also includes a positive electrode plate and a negative electrode plate; the positive electrode plate includes a positive electrode material, the negative electrode plate includes a negative electrode active material layer, and the negative electrode active material layer includes a negative electrode material; the positive electrode material includes at least one of lithium nickel cobalt manganese oxide and doped lithium nickel cobalt manganese oxide; the negative electrode material includes a silicon-based material.
8. The secondary battery according to claim 7, characterized in that: The molar percentage of nickel in the positive electrode material to the transition metal elements is ≥90%, and / or the mass percentage of silicon in the negative electrode active material layer is 0.5-12.5%.
9. The secondary battery according to claim 8, characterized in that: In the electrolyte, the mass percentage of silicon element in the negative electrode material layer is ≥10%, and the mass percentage of the second additive in the electrolyte is 0.3-0.5%.
10. The secondary battery according to claim 9, characterized in that: The secondary battery satisfies: T*b=14-250, wherein T°C is the temperature corresponding to the first exothermic peak when the negative electrode plate is subjected to differential scanning calorimetry at 0-400°C.
Citation Information
Patent Citations
High-temperature non-aqueous electrolyte solution and secondary battery
CN115588779A
Battery, power utilization system and energy storage system
CN117954690A
Lithium ion battery electrolyte and lithium ion battery
CN118431564A
Non-aqueous electrolyte for lithium ion battery and lithium ion battery
CN119153779A
Panel sprinkler system on the wall
KR102306801B1